BOOK REVIEW MARITIME SECURITY AND INDONESIA: COOPERATION, INTERESTS AND STRATEGIES - Darmawan, Aristyo Rizka (Indonesia Law Review, 2020)
Senia Febrica in her book Maritime Security and Indonesia: Cooperation, Interests, and strategies provides a deep analysis of the maritime security challenges of Indonesia and how Indonesia responds to it. Indonesia as the largest archipelagic states in the world with a vast maritime zone ranging from archipelagic water, internal water, contiguous zone, continental shelf, and exclusive economic zone are facing a lot of threat from outside as well from inside Indonesia. Moreover, the fact that Indonesia is located in a strategic location for international trade routes such as Malacca strait made Indonesia’s strategies in dealing with maritime security threats more important.